Detection of porcine pepsin in model cheese using polyclonal antibody-based ELISA - Raja Nhari, Raja Mohd Hafidz; Muhammad Zailani, Azyan Nafisah; Khairil Mokhtar, Nur Fadhilah; Warsanah, Irwan Hanish (Taylor and Francis, 2020)
The usage of porcine pepsin or other porcine derivatives in food products is a common practice in European, American and certain Asian countries although it creates issues in religious and personnel health concerns. In this study, porcine pepsin was detected using indirect ELISA that involved the anti-pep80510 polyclonal antibody raised against a specific peptide of porcine pepsin, pep80510. The sensitivity of the assay for standard porcine pepsin was 0.008 µg/g. The immunoassay did not cross-react to other animal rennet and milk proteins except for microbial coagulant from Mucor miehie. The recovery of porcine pepsin in spiked cheese curd within the range of CV < 20% while for porcine pepsin in spiked cheese whey the recovery is also within the range of CV% < 20%.